Evidence for Resilient Agriculture informs more than USD 1 billion in investment plans and guides evidence-based policy, programming and capacity building in Africa - CGIAR Research Program on Climate Change, Agriculture and Food Security (2020)
Synthesized data and analyses from the Evidence for Resilient Agriculture (ERA) meta-dataset were used to (i) develop multi-million-dollar climate-smart investment plans in Mali, Cote d'Ivoire, Ghana, Burkina Faso, (ii) inform the adaptation portfolio of the Gates Foundation, (iii) design three county adaptation plans in Kenya, (iv) inform the design of a Green Climate Fund (GCF) project led by the International Union for the Conservation of Nature (IUCN) and Government of Tanzania and (v) build capacity for NDC implementation across Africa.